Tools for Anopheles gambiae Transgenesis. Issue 6 (1st June 2015) - Volohonsky, Gloria; Terenzi, Olivier; Soichot, Julien; Naujoks, Daniel A; Nolan, Tony; Windbichler, Nikolai; Kapps, Delphine; Smidler, Andrea L; Vittu, Anaïs; Costa, Giulia; Steinert, Stefanie; Levashina, Elena A; et al.
Abstract: Transgenesis is an essential tool to investigate gene function and to introduce desired characters in laboratory organisms. Setting-up transgenesis in non-model organisms is challenging due to the diversity of biological life traits and due to knowledge gaps in genomic information. Some procedures will be broadly applicable to many organisms, and others have to be specifically developed for the target species. Transgenesis in disease vector mosquitoes has existed since the 2000s but has remained limited by the delicate biology of these insects. Here, we report a compilation of the transgenesis tools that we have designed for the malaria vector Anopheles gambiae, including new docking strains, convenient transgenesis plasmids, a puromycin resistance selection marker, mosquitoes expressing cre recombinase, and various reporter lines defining the activity of cloned promoters. This toolbox contributed to rendering transgenesis routine in this species and is now enabling the development of increasingly refined genetic manipulations such as targeted mutagenesis. Some of the reagents and procedures reported here are easily transferable to other nonmodel species, including other disease vector or agricultural pest insects.